Assumptions and Reality: The securitisation of human trafficking in Southern Africa - Hübschle, Annette (Institute of Criminology, 2014)
Our understanding of the concept of security has changed since the end of the Cold War. A cursive look at our daily news headlines confirms that a plethora of phenomena are phrased in security terms. The 'drug on wars' and the 'global war on terrorism' are the most obvious examples. Trafficking in persons has also been elevated to a security issue. The trend of 'securitising' non-traditional security threats has not stirred much controversy as yet. This dissertation will question why and how the issue of human trafficking has been securitised. In using the Copenhagen School's securitisation theory as an analytical framework, the dissertation will examine the international and regional (southern Africa) dimensions of the securitisation of human trafficking. The emergence of human trafficking as a social problem in public discourse will be discussed. Of principal concern are the underlying interests that propel the moral panic. Another chapter will look at global strategies aimed at combating and preventing trafficking. Before exploring the parallels between the 'Global War on Terrorism' and the dominant anti-trafficking paradigm, existing research evidence on the prevalence, scale and size of human trafficking will be scrutinised.